The Creative Use of Cohesive Devices: Exploring New Roles - Abu-Ayyash, Emad A. S. (2020)
The role of cohesive devices in different types of discourses has been broadly acknowledged to be maintaining texture, or holding the different parts of the text together. This role was emphasised in a plethora of studies in discourse analysis, and cohesive devices have been considered to be the glue-like linguistic tools through which textuality is achieved and without which a certain piece of discourse would look like fragmented, disconnected sentences. Important as it is, the ‘gluing’ role of cohesive devices has been the primary and dominant focus of research and whether these devices can play other roles in texts has been under-investigated, if not ignored. The current paper addresses this gap in research by exploring other possible roles of cohesive devices. Three newspaper, opinion articles for one of the renowned writers, Thomas L. Friedman, were selected and analysed in terms of the various roles played by cohesive devices in them. Through mixed-methods analysis, it was found that cohesive devices played several roles other than holding the various parts of the text together.